Comparison of Genexpert MTB/RIF Assay and AFB Smear Microscopy in Diagnosis of Pulmonary Tuberculosis among HIV Patients at a Tertiary Care Hospital - Bajracharya, Najma; Paudyal, Rabin; Bastola, Anup (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2022)
Introduction: Tuberculosis (TB) has been the most common acute opportunistic infection in HIV positive patients and accounts for more than half of all AIDS cases in underdeveloped nations. Hence, rapid laboratory diagnosis of M. tuberculosis is needed for vulnerable patients. Methodology: In this study, 72 sputum samples were collected from ART-naive and patients using ART for 6 months. The samples were tested with the GeneXpert MTB / RIF assay to diagnose TB and drug resistance and AFB smear microscopy as per NTP guidelines. Results: Among 72 sputum samples studied, males were more diagnosed with TB than females. People aged 25-56 years were more infected with HIV-TB co-infection. Four patients (5.56%) were found to be TB positive with both techniques, 7 (9.72%) were GeneXpert MTB/RIF positive but smear-negative and 61 patients (84.72%) were negative with both methods. The positivity for MTB detected for GeneXpert MTB/RIF method in females was 3 (15%) and the males were 8 (15.38%), while for the ZN staining method the positivity in females was 2 (10%) and the males were 2 (3.85%). The GeneXpert MTB/RIF assay was also capable of detecting TB in smear-negative cases. Conclusion: This study showed that the GeneXpert MTB/RIF assay is an effective tool for the early diagnosis of TB among HIV patients as compared to AFB smear staining method.